Examining the response of house prices to supply using a Markov regime switching approach: The case of the Irish housing market - Paul Egan; Kieran McQuinn (The Economic and Social Research Institute (ESRI), 2022)
Understanding the impact of housing supply on housing price inflation is a particularly important issue from a policy-maker's perspective. Notwithstanding the impact of the great financial crisis (GFC) in 2007/08, the past 25 years has seen a significant increase in housing prices across a number of western economies. More recently, across countries, a common characteristic observed in housing markets appears to be the increase in price inflation in the aftermath of the Covid-19 pandemic. A key question which arises is whether housing price inflation can be assuaged somewhat by greater levels of housing supply? In this paper, we seek to quantify the impact of additional supply on price inflation in the Irish property market. While residential property markets in many countries experienced substantial swings in activity since the early 1990s, the Irish market has demonstrated particular volatility. Crucially, therefore, we address this question using both a multiple breakpoint model and a Markov switching model to allow for the presence of structural changes in the Irish residential market over the period 1981 to 2019. Our results indicate that additional supply does indeed exert a negative impact on prices, however, the impact varies over time.
Keywords: E42; E51; R31; 330; Housing Prices; Housing Supply; Breakpoints; Markov switching